2014
DOI: 10.1016/j.humov.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of instruction to synchronize over step frequency while walking with auditory cues on a treadmill

Abstract: Walking to a pacing stimulus has proven useful in motor rehabilitation, and it has been suggested that spontaneous synchronization could be preferable to intentional synchronization. But it is still unclear if the paced walking effect can occur spontaneously, or if intentionality plays a role. The aim of this work is to analyze the effect of sound pacing on gait with and without instruction to synchronize, and with different rhythmic auditory cues, while walking on a treadmill. Firstly, the baseline step frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 19 publications
4
35
2
Order By: Relevance
“…This finding is consistent with previous studies in healthy controls (HCs) and in persons with PD as well. Yet, in these studies, the motor thresholds where participants were asked to walk was set at either 5%, 10%, and 10%, 15% above or below their usual walking frequency. Furthermore, studies investigating spontaneous synchronization reported that only 50% of participants synchronize spontaneously, and only at tempos close to their usual walking frequency, or 2% above this frequency; these thresholds are termed as the entrainment basin …”
Section: Introductionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with previous studies in healthy controls (HCs) and in persons with PD as well. Yet, in these studies, the motor thresholds where participants were asked to walk was set at either 5%, 10%, and 10%, 15% above or below their usual walking frequency. Furthermore, studies investigating spontaneous synchronization reported that only 50% of participants synchronize spontaneously, and only at tempos close to their usual walking frequency, or 2% above this frequency; these thresholds are termed as the entrainment basin …”
Section: Introductionsupporting
confidence: 94%
“…To differentiate these types, a recent study investigated if healthy subjects synchronized their steps to music when uninstructed and instructed, and concluded that instruction was required for synchronization to occur. 11 This finding is consistent with previous studies in healthy controls (HCs) and in persons with PD 12,13 as well. Yet, in these studies, the motor thresholds where participants were asked to walk was set at either 5%, 10%, 13 and 10%, 15% 11 above or below their usual walking frequency.…”
Section: Introductionsupporting
confidence: 92%
“…Second, we employed a novel integrated audio-playlist strategy where patient preferences informed the choices of musical genres and artists but where exercise pace restricted the playlist selection to those songs whose music tempos approximated individuals’ program-prescribed steps per minute. Third, our study demonstrated that RAS-enhancements, which were designed to accentuate the auditory cues associated with tempo-pace synchrony [24,27], were accomplished feasibly using commercially available customized playlists. Moreover, such RAS-enhanced playlists were incrementally efficacious in improving long-term physical activity behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency was controlled by a digital metronome (Korg TM-50) at fifty and eighty pulses per minute for the low and high condition, respectively. Before determining the low and high frequency, the participants performed several trials to select their preferred low and high walking frequency (Mendonça, Oliveira, Fontes, & Santos, 2014;Picelli et al, 2010). Data obtained from these attempts allowed us to calculate the mean and fix the same frequency (due to the similarity) for the entire sample.…”
Section: Methodsmentioning
confidence: 99%